P08 Risk of invasive pneumococcal disease in children with sickle cell disease in england: National observational cohort study, 2010 – 2015. (24th May 2017) - Oligbu, G; Collins, S; Streetly, A; Dick, M; Ladhani, S
Abstract : Introduction: Invasive pneumococcal disease (IPD) is the leading cause of morbidity and mortality in children with sickle cell disease (SCD). We describe the risk, clinical presentation, serotype distribution and outcomes of IPD in children with SCD following the introduction of the 13-valent pneumococcal conjugate vaccine (PCV13) in the United Kingdom based on a complete cohort and accurate denominator of affected cases. Methods: The Newborn screening programme cohort study of sickle cell disease was established in 2010 and is currently based at King's College London. All screen positive results from the screening programme of infants born between 01 September 2010 to 30/08/2014(four years) were followed-up until 31/12/ 2015. The cohort study identified a number of deaths from IPD in the affected children. In conjunction with Public Health England (PHE) which conducts enhanced national surveillance in England and Wales of all laboratory-confirmed IPD cases in <5 year-olds, it was possible to obtain an accurate denominator of affected cases and to calculate the risk of IPD in children with sickle cell disease. Results: Eleven children with sickle cell disease, including nine with HbSS who developed IPD during the surveillance period. Median age at IPD was 13 months, serogroup 15(not present in PCV 13) was responsible for 73% (8/11) of IPD cases and three children (27%) died. Infants and children with SCD had a 35.6fold (1, 571/100, 000 vs. 44/100, 000; IRR, 35.6; 95% CI, 19.7– 64.2, p<0.00001) higher risk of IPD compared with national IPD incidence in the same age-cohort and over the same surveillance period. Conclusions: Children with SCD remain at increased risk of IPD despite being identified at birth and being prescribed prophylactic antibiotics by 3 months of age and conjugate pneumococcal vaccine as part of the universal immunisation programme. They are also more likely to die of their infection. It was of concern that most cases are now due to serotypes not covered by PCV13 although covered by the 23 valent Pneumovax offered at 2 years of age. Parents will need to understand the crucial importance of antibiotic prophylaxis and both parents and professionals will need to remain vigilant in identifying IPD in this group of children.